Luteolin peracetate and gossypolone inhibit immune complex-mediated neutrophil activation in vitro and dermal-epidermal separation in an ex vivo model of epidermolysis bullosa acquisita - Yang, Kai; Yin, Junping; Yue, Xiaoyang; Bieber, Katja; Riemekasten, Gabriela; Ludwig, Ralf J.; Petersen, Frank; Yu, Xinhua (Frontiers in Immunology, 2023)
Natural products have been shown to an important source of therapeutics for human disease. In this study, we aimed to identify natural compounds as potential therapeutics for epidermolysis bullosa acquisita (EBA), an autoimmune disease caused by autoantibodies to type VII collagen (COL7). Utilizing an in vitro experimental system, we screened a natural product library composed of 800 pure compounds for their inhibitory effect on COL7-anti-COL7 IgG immune complex (IC)-mediated neutrophil activation. Three natural compounds, namely luteolin peracetate, gossypol, and gossypolone were capable in inhibiting the IC-induced neutrophil adhesion and oxygen burst in vitro. Furthermore, luteolin peracetate and gossypolone were able to inhibit the anti-COL7 IgG induced dermal-epidermal separation in an ex vivo model for EBA.In summary, this study demonstrates that luteolin peracetate and gossypolone are potential therapeutics for experimental EBA, which deserves further investigation.